1-Nicotinoylbenzotriazole: A Convenient Tool for Site-Selective Protection of 5,7-Dihydroxycoumarins - Fatykhov, Ramil F.; Khalymbadzha, Igor A.; Chupakhin, Oleg N.; Charushin, Valery N.; Inyutina, Anna K.; Slepukhin, Pavel A.; Kartsev, Victor G. (Synthesis, 2019)
1-Nicotinoylbenzotriazole (NicBt) was uncovered as an efficient protecting agent for the site-selective acylation of resorcinol-type phenolic groups with almost equal reactivity. The use of NicBt allows selective protection of the 7-OH group in 5,7-dihydroxycoumarins in one simple scalable step, while combination of the nicotinoylation with tosylation–denicotinoylation or silylation–denicotinoylation yields 5-OH-protected 5,7-dihydroxycoumarins. Furthermore, nicotinoylated 5,7-dihydroxycoumarins proved useful in a gram-scale three-step preparation of a 2,2-dimethylpyrano[2,3-f]coumarin, a key intermediate for the synthesis of calanolide A, an HIV reverse transcriptase and Mycobacterium tuberculosis inhibitor, and its active analogues.
Keywords: esterification; protecting groups; phenols; acylation; natural products; total synthesis